Transforming enterprise education : sustainable pedagogies of hope and social justice - Drakopoulou Dodd Sarah; Jack Sarah; Verduijn Karen; Hytti Ulla; Berglund Karin; Lage-Arias Serxia (Taylor & Francis, 2022)
Building on Alistair Anderson's work, this paper proposes transforming enterprise education to deeply address questions of sustainability, social justice and hope in our time of multiple and complex crises. New pedagogies, practices, vocabularies and connections help us to enact crises in entrepreneurial, ethical and creative ways, enabling us to remain hopeful in the face of unknown horizons. Drawing from critical pedagogies, from Epistemologies of the South, and from the wisdoms of Alistair Anderson, the paper outlines how transforming to a more, hopeful, socially-just, and sustainable enterprise education could move us beyond present alternatives. We suggest that transforming enterprise education (TrEE) would better facilitate students as ethical change-makers when they engage with their worlds, and its unseen future horizons. TrEE emphasises the time needed for questioning dominant meanings and space for experimenting with new ones. It invites re-placing us in the margins and with the excluded. It takes an expansive view of the ecosystem, and places enterprise within its wider context. It focuses students, teachers, entrepreneurs and various other stakeholders in learning together with the non-human and relies on sustainable stewardship, social justice and hope at the core of transforming enterprise education.